Indian insects : diversity and science - Ramani, S., 1955-; Yeshwanth,H.M.; Mohanraj,Prashanth (Boca Raton : CRC Press, 2019)
"Insects are useful as pollinators of crops and wild plants and many are useful as natural enemies of pestiferous insects. It is important to conserve these insects, hence there is a need for reliable identification techniques for these insects. This volume brings together indigenous taxonomic expertise on various taxa of insects from India"--
Includes bibliographical references and index.
Keywords: Insects -- India; Insects -- Conservation